RANCANG BANGUN E-COMMERCE PENJUALAN BUAH MENGGUNAKAN METODE CUSTOMER RELATIONSHIP MANAGEMENT (CRM) - Laras Avisya (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2023)
Fruit is one of the horticultural crops that plays an important role in improving the quality of nutrition for humans. Fruit also contains many vitamins and minerals that are beneficial to human health. One complete Fruit Shop in providing fresh fruit is "Nop Fruit". However, the Nop Fruit Fruit Shop still relies on face-to-face contact with customers in conducting its sales. The basic problem at the Nop Fruit Fruit Shop is the lack of effort in promotion so that sales become very low and unstable. The store also often suffers big losses during the rainy season because there are not enough buyers and the fruit is spoiled. One strategy that can be used to increase sales and face intense business competition is the Customer Relationship Management (CRM) strategy. CRM can help maintain good relations with consumers, attract buyers and increase customer loyalty. Therefore, with these problems, an e-commerce website for fruit sales is created which can facilitate a faster and more effective transaction process, can also facilitate consumers in order fruit without having to come to the store. With this e-commerce website, it is hoped that Nop Fruit Shop will get bigger profits and can minimize the owner's bad losses by seeing the development of consumer buying interest in the shop.